Electric discharges in water-air medium for treatment of aqueous solutions with high electric conductivity - Osokin G. E.; Kornev Ya. I. Yakov Ivanovich; Galanov A. I. Andrey Ivanovich; Preis S. S.; Yavorovsky N. A. Nikolay Aleksandrovich; Ushakov V. Ya. Vasily Yakovlevich (2012, 2012)
В фонде НТБ ТПУ отсутствует